CHAUPI ÑAMCA: TAKISCANTARI RUMICUNAMANDA HUARMIHUACA - Sandoval, Sergio Andrés (2011)
This article studies the myths of the goddess Chaupi Ñamca in the Andean manuscript from the seventeen century, written in the region of Huarochiri (today Peru), and their relation with ritual, feminine, geographic and divine conceptions of the native cultures. The mythic figure of Chaupi Ñamca, as mother, huaca and stone, is related to the Chaucosma dances, the aboriginal resistance and the fertility rituals. Based on the approximation to words and concepts from the quechua language, the objects of study are the chapters dedicated to this Andean goddess that symbolizes sexuality, fertility and woman. Finally, the article proposes a path of investigation about the Andean thought, the writing and the mythology in the anonymous manuscript of Huarochiri.